The use of adverbials in the verbal production of Malay ESL learners: a processability approach - Wan Adnan, Wan Nur Asyura; Mohammad Lotfie, Maskanah (Universiti Teknologi Malaysia, 2017)
This study investigates the development of verbal usage of adverbials by Malay ESL learners at the tertiary level. It aims to find out the developmental differences between low and intermediate learners’ acquisition of adverbials. Using Processability Theory (Pienemann, 1998; 2005) and taxanomy of adverbials (Celce-Murcia & Larsen-Freeman, 1999) as the frameworks, this study explains the extent to which Malay ESL learners at the tertiary level have developed their use of English adverbials. For data collection purposes, a picture-cued task was administered on 60 Malay ESL students in which they were required to elicit each process in each picture. The results indicate that, in terms of their use of adverbials, most of the Malay ESL students from both proficiency levels were considered to have reached Stage 6 of the Processability Theory developmental stages and only a number of elementary level students were found to have only reached Level 2. The findings suggest that ESL practitioners should follow the developmental routes suggested by the Processability Theory in teaching grammar components to students.